Penafsiran Sufistik-Kejawen atas Surah Al-Fatihah: Studi Analisis atas Manuskrip Kiai Mustojo - Muhammad Masrofiqi Maulana (Manuskripta, 2020)
Abstract: Some interpreters in Java tend to use the mystical style of tasawwuf-kejawen to interpretate the Quran. One of the interpreters is Kiai Mustojo, Campurejo, Sambit, Ponorogo. This article presents the theory of tasawwuf and sufi interpretation, the manungguling kawula-Gusti concept, Kiai Mustojo manuscript identification, and the analysis of manunggaling kawula-Gusti concept in the Kiai Mustojo’s interpretation on al-Fatiha. This interpretation is once of historical evidence that there is an intense contact between Islamic teaching and Javanese mysticism in the inland of Java and it’s as legitimation of his mystical-Kejawen teachings. His interpretation will always reveal the meaning behind the literal meaning of a word in al-Fatiha. Even though, it has a meaning more than connotative meaning, it doesn’t mean the denotative meaning that exist in the Quran is not so important. It causes the connotative meaning becomes a gateway for the entrance to understand of other meanings. --- Abstrak: Beberapa mufassir di Jawa cenderung menggunakan corak tasawuf mistik kejawen dalam menafsiri Alquran. Salah satu penafsir yang menggunakan sufistik-kejawen dalam melakukan pembacaan atas Alquran adalah Kiai Mustojo, Campurejo, Sambit, Ponorogo. Artikel ini menampilkan teori tasawwuf dan penafsiran sufi, konsep manunggaling kawula-Gusti, identifikasi naskah Manuskrip Kiai Mustojo dan analisa konsep manunggaling kawula-Gusti dalam penafsiran Kiai Mustojo atas surah al-Fatihah. Penafsiran Kiai Mustojo ini menjadi salah satu bukti historis bahwa adanya hubungan yang begitu intens antara ajaran Islam dan ajaran mistik Jawa di Pedalaman Jawa serta merupakan legitimasi akan ajaran-ajaran mistik Kejawennya. Penafsirannya akan selalu mengungkap makna di balik makna literal sebuah kata dalam al-Fatihah. Meski memiliki makna yang lebih dari makna konotatif, bukan berarti makna denotatif yang ada dalam Alquran tidak begitu penting. Sebab makna literal dari sebuah kata yang ada dalam Alquran menjadi pintu gerbang bagi masuknya pemahaman terhadap makna lain.